Islamic perspectives relating to business, arts, culture and communication: Proceedings of the 1st ICIBACC 2014 - Omar, Roaimah (Springer, 2015)
This timely book explores how the Malays and Muslims in general are faced with challenges in the fields of business, economy and politics, in the modern era of globalisation. These research findings can help the Muslim community to enhance international integration, particularly in Malaysia and Southeast Asia.